PERBANDINGAN HUKUM BANK KONVENSIONAL DENGAN BANK SYARI’AH DALAM MEMBERIKAN KREDIT ATAU PEMBIAYAAN PADA NASABAH DI KOTA BUKITTINGGI ( PADA BANK MANDIRI DAN BANK SYARI’AH MANDIRI KOTA BUKITTINGGI ) - Suhardi M.Ag (Menara Ilmu, 2016)
This research is a study of Conventional Banks and Shariah Banks in providing credit to Customers. In the State of Indonesia there are two types of banks, namely, the first is a conventional bank with an interest system and the second is a syariah bank with a profit sharing system. At this Bank there are fundamental differences when viewed from the way the Bank distributes funds to the public, the Conventional Bank that we are familiar with the interest system and the Sharia Bank with the profit sharing system. The focus of the problem in this research is the similarities and differences between Conventional Banks and Sharia Banks in financing or crediting customers, and which banks are preferred by the public in conducting banking activities. In this study the authors use the Legal Juridical Sociological method which is a study that emphasizes the legal aspects (applicable legislation) regarding the issues to be discussed and how the implementation of the written provisions in the field, the authors also use interview techniques to find out how the bank's performance in practice. Based on the results of the study it can be concluded that basically the Conventional Bank and the Sharia Bank are equally channeling funds to the public, the fundamental difference is the financial principles used, namely the Conventional Bank with interest and Sharia Bank with profit sharing. Another difference is in the sector that can be financed. At Conventional Banks all sectors can be given credit, but at the Sharia Bank the sector to be financed must be a halal sector, so that the money given and received by the Bank is something that is lawful in accordance with Islamic Sharia. Keywords: Comparison, Banks, Conventional, Shariah.